The relationship between coronary atherosclerosis and body fat distribution measured using dual energy X-ray absorptiometry. (May 2016) - Park, Se-Jun; Yang, Hyoung-Mo; Seo, Kyoung-Woo; Choi, So-Yeon; Choi, Byoung-Joo; Yoon, Myeong-Ho; Hwang, Gyo-Seung; Tahk, Seung-Jea; Sheen, Seung-Soo; Choi, Byung-il W.; Lim, Hong-Seok
Abstract: Objective: Body fat distribution is closely related to cardiovascular diseases. We aimed to evaluate the relationship between truncal fat distribution and the extent of coronary atherosclerosis. Methods: Total body fat and regional body fat distributions were measured using dual-energy X-ray absorptiometry (DXA) in 746 Korean patients who underwent coronary angiography. The ratios of truncal fat mass to total body fat mass (FMtrunk /FMtotal ), truncal fat mass to fat mass in both legs (FMtrunk /FMleg ) and truncal fat mass to fat mass in both arms (FMtrunk /FMarm ) were calculated as representative parameters for truncal fat accumulation. The extent of coronary atherosclerosis was assessed using the Gensini score. Results: The mean Gensini score of the patients was 21.3 ± 24.4. FMtrunk /FMtotal, FMtrunk /FMleg and FMtrunk /FMarm revealed positive correlations with the Gensini score (r = 0.242, p < 0.001; r = 0.219, p < 0.001; r = 0.133, p < 0.001, respectively). In contrast, body mass index (BMI) and total body fat mass did not correlate with the Gensini score. On multiple regression analysis, FMtrunk /FMtotal was associated with the Gensini score independently of age, gender, BMI and major risk factors of coronary heart disease (B = 0.039, p < 0.001). Conclusion: Truncal fat distribution is associated with the extent of coronary atherosclerosis and more clinically relevant to that compared with total body fat or BMI in Korean patients. Highlights: The relationship between body fat distribution in the trunk and severity of coronary atherosclerosis has not been proved. The truncal fat distribution, reflecting accumulation of abdominal fat and thoracic fat in an integrated manner, is relevant to the coronary atherosclerotic extent. Active therapeutic interventions for the truncal fat accumulation might be important to prevent coronary atherosclerosis.